The Effect of Parents' Cost of Education and Social-Economic Status on Interest in Continuing Education to Higher Education in Students of Class XII IPS SMAN 8 Jambi - Rosmiati Rosmiati; Siti Syuhada; Anneke Puspita (Social Studies Conference Proceedings, 2021)
This study aims to determine whether there is a significant influence between Education costs for interest in continuing their education in tertiary institutions, (2) parents' socioeconomic status on their interest in continuing their education in tertiary institutions, (3) educational costs and parents' socioeconomic status on their interest in continuing their education to tertiary institutions. This research is quantitative research with a quantitative descriptive research type. The population in this study was 75 people, namely students of class XI IPS. The study results show that: (1) There is an effect of the cost of education on the interest in continuing education to higher education as indicated by the value of tcount 4.902 > ttable 1.66600. (2) There is an influence of parents' socioeconomic status on their interest in continuing their education to higher education as indicated by t count 4.512 > t table 1.66600. (3) There is a simultaneous effect of the cost of education and parents' socioeconomic status on the interest in continuing their education to college. Given the cost of education and parents' socioeconomic status, the interest in continuing their education to college is 43.5%, and the remaining 46.5% is influenced by other variables that are not explained in this research. Based on the research results, it can be concluded that the cost of education and parents' socioeconomic status influence their interest in continuing their education to college.